4 - Matriliny, Patriliny, and Wealth Flow Variations in Rural Malawi - Mike Mathambo Mtika; Henry Victor Doctor (African Sociological Review, 2002)
Literature on African kinship political economies suggests that under matriliny, wealth flow would be biased towards a matrilineal line in that children would engage in transfers with their maternai more than their paternal relatives. Under patriliny, the reverse would be the case. We explore these propositions using data from a sample survey of 1257 respondents in rural Malawi, 29 percent of whom were from a predomi nantly matrilineal ethnie group, 36 percent werefrom an ethnie group that is transformingfrom matrilineal to patrilineal practices, and 35 per cent were from a patrilineal ethnie group. These data were comple mented by qualitative interviews of 18 respondents from the matrilineal ethnie group, 20 from the transforming group, and 18 from the patrilineal group. Results reveal little evidence to support the propositions. We think that the increasingprivatisation of production and consumption, that has over the years penetrated rural Malawi, has led to some individualistic tendencies among rural Malawians and weakened both matrilineal and patrilineal influence on people 's wealth transfer behaviours.